Fabrication and Testing of a Low-Cost Wind Turbine Blade using Bamboo Reinforced Recycled Plastic - Prince Yaw Andoh; Charles Kofi Kafui Sekyere; Godwin Kafui Ayetor; Michael Nii Sackey (Journal of Applied Engineering and Technological Science (JAETS), 2021)
Wind energy, as a sustainable energy option is gaining research attention due to its price competitiveness relative to conventional energy sources. This study presents the fabrication and testing of a low-cost wind turbine blade using bamboo fibre with recycled plastic. Bamboo fibre was extracted from raw bamboo and combined with adequately conditioned Recycled High-Density Polyethylene (RHDPE) to form a composite which is 25% bamboo fibre and 75% RHDPE. The composite materials was then used to fabricate a turbine blade which was tested and the results compared with typical performance indices for a turbine blade made of fibre glass for comparative analysis. The turbine blades were installed at a height of 10 meters at the test site and monitored. Results showed the energy per unit cost (kWh) for the composite material was lower than that of the glass fibre with a life cycle of 107 for glass fibre and 106 cycles for the bamboo plastic. Stress and deformation analysis showed a higher value for glass fiber compared with the composite material. It can be deduced that composite material matrix possesses the desired properties and energy per unit cost ratio for consideration in building wind turbine blades.